Agile Project Governance, Knowledge Sharing, and Software Delivery Performance in Vietnamese Tech Startups: The Mediating Role of Sprint Discipline - Lê Thị Hồng Nhung; Trần Minh Khoa (Oikonomia Review: A Journal of Applied Management, Accounting, and Business Strategy, 2026)
Agile methods are widely adopted by Southeast Asian startups to accelerate product development, yet many teams struggle to sustain predictable delivery as organizational complexity grows. This study examines how agile project governance influences software delivery performance in Vietnamese tech startups through knowledge sharing and sprint discipline. Drawing on project governance theory, knowledge-based view, and agile execution research, the model conceptualizes agile governance as lightweight controls that clarify decision rights, align priorities, and manage stakeholder change without undermining autonomy. Survey data were collected from 372 agile teams across Vietnamese tech startups engaged in web and mobile product development. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to test direct effects and parallel mediation. Results indicate that agile project governance strengthens knowledge sharing and sprint discipline; sprint discipline and knowledge sharing each improve delivery performance; sprint discipline partially mediates the governance–performance link and also transmits the effect of knowledge sharing on performance. The findings suggest that startups achieve agile speed when governance builds execution discipline and learning routines rather than imposing bureaucracy. Practical implications emphasize establishing clear backlog ownership, explicit definition-of-done standards, and structured retrospectives that convert knowledge sharing into stable delivery.